Concurrent Displacements: Return, Waiting for Asylum, and Internal Displacement in Northern Mexico. (March 2023) - Gil-Everaert, Isabel; Masferrer, Claudia; Chávez, Oscar Rodríguez
This paper explores the ways in which contemporary mobility dynamics in Mexico have changed over the last decade, leading to protracted displacement. It focuses on three populations: (1) the internally displaced due to violence; (2) Mexican nationals returning from the United States, both voluntarily and due to deportation; and (3) populations seeking asylum in Mexico and the United States. These three populations are not usually analyzed together and do not squarely fall under the traditional legal definitions. The paper outlines ways that situations of protracted displacement and insecurity present challenges in four interconnected arenas of life: housing, legal status, employment, and emotional well-being. For governments and local communities, protracted displacement requires immediate humanitarian responses and the development and implementation of public policies focused on integration. The paper concludes with a set of policy recommendations based on its findings.